PERAN FINTECH DALAM OPTIMALISASI PENERIMAAN PAJAK MELALUI INOVASI PEMBAYARAN - Widjaja, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The development of digital technology has driven significant transformation in Indonesia's financial and taxation systems. Financial technology (fintech) has emerged as an innovation that facilitates access to financial services and payment transactions, including tax payments. This study aims to analyse the role of fintech in optimising tax revenue through digital payment innovations. Using a qualitative approach through literature review and regulatory analysis, this study found that the integration of fintech into the taxation system can expand the tax base, increase transparency, and significantly encourage taxpayer compliance. The digital payment innovations introduced by fintech not only accelerate the tax payment and reporting process but also facilitate the government in monitoring and managing state revenue in real time. However, challenges related to regulatory harmonisation, data protection, and digital literacy among the public still need to be addressed in order to optimise the potential of fintech in supporting an inclusive and efficient taxation system in Indonesia.